(untitled) (Journal of Life and Earth Science, 2012)
The study conducted an empirical investigation on self-concept as related to gender, parental profession and academic achievement among early-adolescent boys and girls in various institutions of Rajshahi city. A total of 160 respondents constituted the sample of the study. A 2×2×2 factorial design involving two levels of gender (boy/girl), two levels of parental profession (service/business) and two levels of academic achievement (high achiever/low achiever) were used. The results showed significantly higher self-concept of girls than boys. In case of academic achievement high achievers expressed significantly more positive self-concept than low achievers. In case of parental service, high achiever boys and high achiever girls expressed significantly more positive self-concept followed by their counterpart low achievers. In case of parental business, it was found that high achiever girls expressed significantly more positive self-concept than low achiever girls. However no significant mean difference was obtained between high achiever boys and low achiever boys in case of parental business. Thus, self-concept of young children was found to be determined by gender, parental profession and academic achievement during early adolescent stage. DOI: http://dx.doi.org/10.3329/jles.v6i0.9728 JLES 2011 6: 97-103